The effect of 4-week fish oil supplementation on peripheral fatigue and recovery induced by incremental exhaustive activity in young healthy men - Roya Zekri Kondelji; Vahid Sari Sarraf; Maryam Nourshahi (Shahid Beheshti University, 2021)
Purpose: Increasing cytokines is one of the body responses to exercise. The effect of inflammation on chronic fatigue syndrome is obvious but its effect on exercise induced fatigue and recovery is unknown. Therefore, this study was performed in order to investigate the effects of 4-weeks of fish oil supplementation on peripheral fatigue induced by incremental exhausting exercise.Methods: For this purpose, 20 healthy men were selected and assigned in fish oil (FO) and corn oil (CO) groups and consumed six gr/day of supplements. Before and after supplementation, peak to peak M-wave amplitudes and maximal voluntary contraction (MVC) of their tibialis anterior muscle were evaluated before, immediately after exercise and also, after 20-min recovery.Results: The results of two-way analysis of the differences of M-wave results didn't show significant differences between groups while significant differences observed in MVC of participants in response to supplementation and after exercise and recovery (P < 0.05). In addition, we observed lower perceived exertion after exercise and supplementation only in FO group (P < 0.05).Conclusion: These results showed that FO can improve muscular performance but this improvement is not due to the improvement in neuromuscular propagation (M-wave), while it can be as a cause of reduce in central fatigue or muscle contractile properties. However, complete understanding of the exact role of inflammation and FO on neuromuscular function still need more investigations.